Case study of the Beijing 2022 Olympic Winter Games: Implications for global mass gathering events amidst the COVID-19 pandemic - Huo, Da; Shen, Ying; Zhou, Tao; Yu, Tong; Lyu, Ruoran; Tong, Ying; Gao, Ting; Wang, Quanyi (Frontiers in Public Health, 2023)
Objective This study aimed to evaluate the public health countermeasures against COVID-19 that are important for organizing mass gathering events (MGEs) during a pandemic and to identify the practices suitable for application at future MGEs. Methods This case study analyzed data from the Beijing 2022 Olympic Winter Games. The analysis was conducted from the viewpoints of overseas stakeholders and Chinese residents. The comprehensive set of countermeasures established to prevent the transmission of COVID-19 comprised the bubble strategy, three-layer testing strategy (pre-departure testing, testing at the airport, and daily screening), mandatory N95 mask wearing, and vaccination. Findings A total of 437 positive cases within the bubble were reported during the Games, of which 60.6% were detected through airport screening and 39.4% were detected through routine screening. Nearly 92.0% of the positive cases were detected within 7 days of arrival, and 80.8% of cases had already been identified before the Opening Ceremony of the Games. Outside the bubble, no Games stakeholders were infected and no spectator contracted COVID-19. The bubble strategy, three-layer testing strategy, wearing N95 masks, and mandatory vaccination are promising countermeasures to prevent the transmission of SARS-CoV-2 during MGEs. Conclusion The public health countermeasures introduced during the Beijing 2022 Olympic Winter Games were proven to be useful. The success of the delivering and organizing of the Games will provide confidence and a public health legacy for future MGEs amidst the pandemic of COVID-19 or future emerging infectious diseases.